2002
DOI: 10.1046/j.1464-5491.2002.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

The oral glucose tolerance test reveals a high frequency of both impaired glucose tolerance and undiagnosed Type 2 diabetes mellitus in primary hyperparathyroidism

Abstract: Our data in a large and modern day pHPT series, with a preponderance of asymptomatic patients, confirm increased insulin resistance and pre-valence of IGT and undiagnosed diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 17 publications
5
70
0
3
Order By: Relevance
“…Therefore, it was impossible to determine which individuals were at high risk of primary hyperparathyroidism or secondary hyperparathyroidism due to vitamin D deficiency. Both of these conditions, which are relatively frequent in elderly people, have been related to an increased risk of abnormal glucose metabolism and diabetes (39,40). Because primary hyperparathyroidism is the first cause of hypercalcemia, the association between serum calcium and risk of diabetes observed in our study could be explained by the presence of individuals with established or incipient primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 49%
“…Therefore, it was impossible to determine which individuals were at high risk of primary hyperparathyroidism or secondary hyperparathyroidism due to vitamin D deficiency. Both of these conditions, which are relatively frequent in elderly people, have been related to an increased risk of abnormal glucose metabolism and diabetes (39,40). Because primary hyperparathyroidism is the first cause of hypercalcemia, the association between serum calcium and risk of diabetes observed in our study could be explained by the presence of individuals with established or incipient primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 49%
“…Previous reports have also shown that patients with diabetes have elevated serum levels of calcium compared with nondiabetic individuals [3][4][5], and that the serum levels of calcium increase even further with decreasing metabolic control [3,4]. Moreover, in diseases with supranormal levels of serum calcium, such as primary hyperparathyroidism, there is a two-to fourfold higher prevalence of NIDDM and prediabetic states than in the general population [4,6,7]. Less is known about the relationship between serum calcium concentration and the two underlying causes of diabetes: insulin sensitivity and defective insulin secretion.…”
Section: Introductionmentioning
confidence: 98%
“…Calcium is an established regulator of GLUT4 expression, a passive transporter essential for peripheral glucose uptake (4). As a consequence, abnormalities in calcium homeostasis could potentially affect glucose metabolism and contribute to the development of T2DM (5).…”
Section: Introductionmentioning
confidence: 99%